DYSMENORRHEA, ADENOMYOSIS, ENDOMETRIOSIS, TUMOR PROCESS: CAUSATION - A. L. Unanyan; I. S. Sidorova; N. A. Nikitina; Y. V. Chushkov; T. D. Guriev; A. D. Nikonets; D. V. Baburin (Медицинский совет, 2017)
The article focuses on the identification of causal relationships between dysmenorrhea, endometrioid and tumor processes. Studies have shown that dysmenorrhea, apart from a decline in the quality of life, can be the cause of development of a number of serious health disturbances, including endometriosis, adenomyosis and even tumoral diseases. Non-steroidal anti-inflammatory drugs are not only the effective means of therapy for dysmenorrhea patients, but also a pathogenetically reasonable approach to prevent the outbreak of the disease.